2012
DOI: 10.1080/13548506.2011.579984
|View full text |Cite
|
Sign up to set email alerts
|

Nonoccupational postexposure prophylaxis following sexual assault in industrialized low-HIV-prevalence countries: A review

Abstract: Although available for over a decade, use of nonoccupational postexposure prophylaxis (nPEP) remains controversial in the United States. There are concerns over sexual assault survivors' adherence, or lack thereof, leading to increased costs without an appreciable decrease in human immunodeficiency virus (HIV) transmission. This review examines and synthesizes the available literature from the past 10 years to determine the true rates of provision and adherence to nPEP regimens in sexual assault survivors in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 52 publications
0
20
0
1
Order By: Relevance
“…For example, as a barrier to routinely offering nPEP, multiple coordinators stated their patients had poor compliance with nPEP and follow-up. This finding was particularly interesting in light of two recent literature reviews that found, on average, 30%–40% of sexually assaulted patients completed the nPEP regimen (Chacko, Ford, Sbaiti, & Siddiqui, 2012; Draughon & Sheridan, 2012). The rates of patients completing nPEP were similar to rates of other patients completing occupational PEP (Luque et al, 2007).…”
Section: Discussionmentioning
confidence: 68%
“…For example, as a barrier to routinely offering nPEP, multiple coordinators stated their patients had poor compliance with nPEP and follow-up. This finding was particularly interesting in light of two recent literature reviews that found, on average, 30%–40% of sexually assaulted patients completed the nPEP regimen (Chacko, Ford, Sbaiti, & Siddiqui, 2012; Draughon & Sheridan, 2012). The rates of patients completing nPEP were similar to rates of other patients completing occupational PEP (Luque et al, 2007).…”
Section: Discussionmentioning
confidence: 68%
“…At Site 2, the significant factor associated with offering nPEP was mode of penile penetration. A recent literature review found in 10 of 14 studies that high-risk exposures (those including anal penetration) were positively associated with offering nPEP (Draughon & Sheridan, 2012). In contrast, there was no significant association between penile penetration and offering nPEP at Site 1.…”
Section: Discussionmentioning
confidence: 99%
“…Only one study incorporated forensic exam findings, however Linden and colleagues found no association between offering nPEP and genital bleeding noted on exam (Linden et al, 2005). Finally, although HIV documentation is usually collected in studies of nPEP after sexual assault, whether a documented HIV risk assessment is associated with offering nPEP has not been assessed (Draughon & Sheridan, 2012). …”
Section: Npep Offered Inconsistently Post-sexual Assaultmentioning
confidence: 99%
“…The Centers for Disease Control and Prevention recommends a post-exposure antiviral prophylaxis ([N] PEP) given up to 72 hours post-assault to reduce the risk of HIV seroconversion [7]. The CDC's 2010 STD Treatment Guideline recommends performing a risk stratification with each SA patient that assesses: the likelihood of the assailant having HIV, any assault-specific exposure characteristics that might increase the risk for HIV transmission, the time elapsed after the event, and the potential benefits and risks associated with the (N) PEP.…”
Section: Introductionmentioning
confidence: 99%